Strategies for Improving Employee Performance Through Strengthening Organizational Culture, Transformational Leadership, and Job Satisfaction at PT Industri Baterai Indonesia Group in Jakarta - Aryo Prabowo Asmoro; Widodo Sunaryo; Herdiyana Herdiyana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Employee performance is a strategic factor in supporting organizational success, including PT Industri Baterai Indonesia (IBC) Group, which plays an important role in the development of the national electric vehicle ecosystem. Differences in employee backgrounds, weak implementation of organizational culture, and suboptimal transformational leadership are thought to affect employee job satisfaction and performance. This study aims to analyze the influence of organizational culture and transformational leadership on employee performance with job satisfaction as an intervening variable. The study uses a quantitative approach through a survey of 113 permanent employees at the low management level of the IBC Group. Data were collected using questionnaires that had been tested for validity and reliability, then analyzed using path analysis techniques using SmartPLS version 4. The results showed that organizational culture and job satisfaction had a positive and significant effect on employee performance, while transformational leadership had a positive but not significant direct effect. Organizational culture and transformational leadership have a positive and significant effect on job satisfaction, as well as a significant indirect effect on employee performance through job satisfaction.